Criminal street gangs and domestic sex trafficking in the United States: evidence from Northern Virginia - Krylova, Yulia (Crime, law and social change, 2023)
The last decade witnessed increasing involvement of criminal street gangs in domestic sex trafficking in the United States. This paper analyzes business models and practices of gang-controlled sex trafficking in Northern Virginia, based on the cases available from PACER, an electronic public access service of the United States federal court. This analysis shows that business models of gang-controlled sex trafficking have become more sophisticated, taking advantages of the globalized financial system, new technology, social media, and the increasing prevalence of illicit commerce in a digital world with greater connectivity. Gangs’ flexible structures combined with loyalty enforced among their members have shielded them from much law enforcement action. The analysis of different gangs involved in sex trafficking in Northern Virginia provides new insights into anti-trafficking policies and law enforcement responses tailored to their structures and modi operandi.